Atrial fibrillation self-management: a mobile telephone app scoping review and content analysis. (11th December 2020) - Pearsons, Alice; Hanson, Coral L; Gallagher, Robyn; O'Carroll, Ronan E; Khonsari, Sahar; Hanley, Janet; Strachan, Fiona E; Mills, Nicholas L; Quinn, Terence J; McKinstry, Brian; McHale, Sheona; Stewart, Stacey; et al.
Abstract: Atrial fibrillation (AF) affects over 1.4 million people in the UK, resulting in a five-fold increased stroke risk and a three to four times greater risk of severe, disabling stroke. Atrial fibrillation, a chronic disease, requires monitoring, medication, and lifestyle measures. A self-management approach supported by mobile health (mHealth) may empower AF self-care. To assess the need to develop new mHealth self-management interventions for those with AF this review aimed to identify commercially available AF self-management apps, analyse, and synthesize (i) characteristics, (ii) functions, (iii) privacy/security, (iv) incorporated behaviour change techniques (BCTs), and (v) quality and usability. We searched app stores for 'atrial fibrillation' and 'anticoagulation', and included apps focused on AF self-management in the review. We examined app functions, privacy statements against best practice recommendations, the inclusion of BCTs using the App Behaviour Change Scale, and app quality/usability using the Mobile App Rating Scale. From an initial search of 555 apps, five apps were included in the review. Common functions were educational content, medication trackers, and communication with healthcare professionals. Apps contained limited BCTs, lacked intuitive functions and were difficult to use. Privacy policies were difficult to read. App quality rated from poor to acceptable and no app had been evaluated in a clinical trial. The review reports a lack of commercially available AF self-management apps of sufficient standard for use in healthcare settings. This highlights the need for clinically validated mHealth interventions incorporating evidence-based BCTs to support AF self-management.